2020
DOI: 10.21203/rs.3.rs-110546/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Lipid-related Effects of Resveratrol on Human Ectopic Endometrial Stromal Cells and a Rat Model of Endometriosis

Abstract: Background: Endometriosis is a complex disease in the field of gynecology that has certain limitations for its interim treatment. Resveratrol has been recently used for the treatment of endometriosis in experimental and clinical studies, but its molecular mechanism remaines elusive. Results: In this study, based on a case-control study, we identified that a decreased BMI and altered lipid profiles were associated with endometriosis patients. We applied resveratrol treatment on human ectopic endometrial stromal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In our previous study, we analyzed the effects of resveratrol treatment on human ectopic endometrial stromal cells. 49 Here, lipidomics analysis showed that resveratrol altered lipid profiles and resulted in changes in glycerophospholipid metabolism pathways and in the activation of insulin resistance. To further confirm, we performed examinations of GTT and ITT, adipocyte histology and flow cytometry of the peritoneal fluid in the EMs rats (Figure4A).…”
Section: Effects Of Resveratrol Manifested By Increased Glucose Tolerance and Enlarged Adipocytesmentioning
confidence: 95%
“…In our previous study, we analyzed the effects of resveratrol treatment on human ectopic endometrial stromal cells. 49 Here, lipidomics analysis showed that resveratrol altered lipid profiles and resulted in changes in glycerophospholipid metabolism pathways and in the activation of insulin resistance. To further confirm, we performed examinations of GTT and ITT, adipocyte histology and flow cytometry of the peritoneal fluid in the EMs rats (Figure4A).…”
Section: Effects Of Resveratrol Manifested By Increased Glucose Tolerance and Enlarged Adipocytesmentioning
confidence: 95%